Indonesian Muslims’ Reception toward Wirid, Zikr and Shalawat during Covid-19 Outbreak; A Mediated Living Hadith - Dewi, Subkhani Kusuma; Huda, M. Johan Nasrul (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This research studies du’a (wirid, zikr and shalawat) that has been practised by Indonesian Muslim to show their response toward Covid-19 outbreak. Using two techniques: survey and interview, this research highlights two model of receptions in living and hadith to understand the practice of du’a. While many consider public ignorance, this research focuses on personal awareness toward the shift of religious gathering (jama’ah) during the quarantine days and their perception of internet- mediated religiosity at the meantime. The result says that the respondents confirm the variability of wirid, zikr, shalawat, such as li khamsatun, shalawat tibbil qulub and doa pagi dan petang. However, their engagement with the internet does not parallel to their authority preference; most of the respondents prefer to grasp ijazah (formally transmission) from the closest family and the surrounded ulama network. A contrasting idea is also seen, as they emphasize face-to face ijazah for their own personal matter, some allow others to take the ijazah digitally.